Non-Financial Reporting in the Light of International Regulations and EU Directives - Ryszard Kamiński, Ryszard (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The need to standardise non-financial reporting to ensure its transparency and clarity is noted by researchers and reporting organisations. In their opinion, the reports should be clear, transparent and comparable and stakeholders should be able to fully satisfy their information requirements. Bearing in mind this assumptions the aim of the study is to analyse the non-Financial reporting system within the scope of international and Eu-ropean Union law. The author pays attention to the essence of reporting non-financial Information and its standards, EU Directives and Guidelines of Discolure.